SOD1-related ALS: what has it told us about motor neuron degeneration? - part 2 - Shaw, Pamela (Henry Stewart Talks, 2022)
Mechanisms of motor neuron injury in the presence of SOD1 mutations, glutamate-mediated excitotoxicity, Determinants of fast and slow disease progression, Therapeutic approaches including gene therapy